Advanced electrochemical detection of amino acids and proteins through flow injection analysis and catalytic oxidation on Prussian Blue. (20th January 2020) - Suprun, Elena V.; Karpova, Elena V.; Radko, Sergey P.; Karyakin, Arkady A.
Abstract: In contrast to the generally accepted point of view that only six proteinogenic amino acids can be directly electrooxidized via their side chains on solid (carbon) electrodes, the specific electrochemical oxidation of nearly all protein amino acids, except for glutamic acid, is revealed with flow injection analysis on bare carbon screen printed electrodes. Furthermore, Prussian Blue was found to catalyze this electrooxidation. For 20 amino acids out of 21 tested, the electrogenerated Berlin Green has been reduced back to Prussian Blue, forming a catalytic cycle that resulted in an increase of oxidation signals. The most effective catalysis – the 54-, 31-, and 11-fold current enhancement – was observed for glutamine, serine, and histidine, respectively. Presently, Prussian Blue seems to be the only known material able to catalyze the specific electrochemical oxidation of nearly all protein-building amino acids and, thus, of all proteins under near-physiological pH conditions (pH 6.0). Edvanced electrochemistry of proteins via specific oxidation of their amino acid residues may open a new avenue for studying protein conformational changes, amino acid substitutions, ligand binding, oxidative damage, and post-translational modifications. Graphical abstract: Image 1 Highlights: Specific oxidation of 20 α, l -amino acids on carbon SPE at 0.95 V was observed, using FIA. Prussian Blue was found able to catalyze the electrooxidation of α, l -amino acids and proteins. Electrogenerated Berlin Green is reduced back to Prussian Blue by an amino acid or its residue.